The Interferon-Gamma +874 A/T Polymorphism Is Not Associated With CMV Infection After Kidney Transplantation - Santiago, Jose Luis; Pérez-Flores, Isabel; Sánchez-Pérez, Luis; Moreno de la Higuera, Maria Angeles; Calvo-Romero, Natividad; Querol-García, Javier; Culebras, Esther; Urcelay, Elena; Fernández-Pérez, Cristina; Sánchez-Fructuoso, Ana Isabel (Frontiers in Immunology, 2020)
The +874 A/T polymorphism in the interferon gamma (IFNG) gene has been associated with Cytomegalovirus (CMV) infection risk in lung and kidney transplant recipients. To replicate this association, we performed a retrospective observational study of this polymorphism and immunosuppression therapies considering the prophylactic treatment in 600 consecutive kidney transplanted recipients. We found no association of aforementioned polymorphism with CMV infection in univariate and multivariate analyses regardless of prophylactic treatment. However, the immunosuppressive treatment with mammalian target of rapamycin inhibitors (imTOR) showed a protective effect in all patients independently of prophylaxis. Moreover, in the adjusted model, we found interactions between prophylaxis with high-risk (D+/R-) CMV status (pinteraction = 0.01), with thymoglobulin induction therapy (p-interaction = 0.03) and with thymoglobulin anti-rejection therapy (p-interaction = 0.002). Data also revealed that in not D+/R-group and no thymoglobulin therapy, the prophylaxis was not an advantage (HR = 0.98, p = 0.95). The benefit of prophylaxis was observed in all groups with thymoglobulin therapy but it was maximal in the group of high-risk CMV status with both thymoglobulin induction therapy and thymoglobulin anti-rejection therapy (HR = 0.01, p < 0.001). In conclusion, IFNG +874 polymorphism is not a predictive marker of CMV infection. The protective effect of mTOR is not improved with prophylaxis. Interestingly, the thymoglobulin therapy associated with prophylaxis is not a risk factor for CMV infection, and prophylaxis is not effective in recipients with no high-risk CMV status and without thymoglobulin therapy.3